TEACHING SPEAKING BY USING ARTIFICIAL INTELLIGENCE (AI)-BASED APPLICATION - Dimas Vega Rizqyqa Putra Budiyono; Mohammad Romadhoni (Journal of English Language Teaching and Islamic Integration, 2024)
This study explores the implementation of the Speechace in teaching speaking. A descriptive qualitative research approach was utilized, incorporating observations, interviews, and questionnaires for data collection. The findings revealed that the Speechace has a speaking test program that users can use for free. At the end of the test, there is a transcription of the assessment which contains sections on speaking skills such as vocabulary, grammar, fluency, coherence and relevance. Apart from that, Speechace also provides free conversation practice. Meanwhile, to use the speaking practice feature provided by Speechace, user can select the "Try in browser" section. After that, various speaking skills will appear that user can try from beginner to intermediate level. In this feature there are lots of conversations and not only words but some are also in the form of sentences which aim to teach students from a low level to a higher level. Thus, the learning process is more engaged with the use of interactive platform.